Nanoparticles in the Treatment of Infections Caused by Multidrug-Resistant Organisms - Nan-Yao Lee; Nan-Yao Lee; Wen-Chien Ko; Wen-Chien Ko; Po-Ren Hsueh; Po-Ren Hsueh (Frontiers Media S.A., 2019)
Nanotechnology using nanoscale materials is increasingly being utilized for clinical applications, especially as a new paradigm for infectious diseases. Infections caused by multidrug-resistant organisms (MDROs) are emerging as causes of morbidity and mortality worldwide. Antibiotic options for infections caused by MDROs are often limited. These clinical challenges highlight the critical demand for alternative and effective antimicrobial strategies. Nanoparticles (NPs) can penetrate the cell membrane of pathogenic microorganisms and interfere with important molecular pathways, formulating unique antimicrobial mechanisms. In combination with optimal antibiotics, NPs have demonstrated synergy and may aid in limiting the global crisis of emerging bacterial resistance. In this review, we summarized current research on the broad classification of the NPs that have shown in vitro antimicrobial activity against MDROs, including the ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species). The pharmacokinetics and pharmacodynamic characteristics of NPs and bacteria-resistant mechanisms to NPs were also discussed.